Analisis keterampilan berpikir kritis peserta didik pada pembelajaran IPA di kelas IV Sekolah Dasar - Mellissa Damayanti; Rukayah Rukayah; Roy Ardiansyah (Didaktika Dwija Indria, 2023)
This study aims to analyze the critical thinking skills of students in science learning in class IV. The method used in this research is qualitative research. The subjects of this study were fourth grade students of SD Negeri 1 Kayugeritan for the 2021/2022 academic year. The data obtained from this study came from the results of tests on students' critical thinking skills in science learning. Test the validity of the data in this study using content validity. The data analysis technique used in this research is using the theory of Miles and Huberman which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are the critical thinking skills of fourth grade students of SD Negeri 1 Kayugeritan are different. There are 20 students who are declared skilled in critical thinking and 7 students who are not yet skilled in critical thinking. Based on the indicators of critical thinking skills, there are still students who have not met these indicators.